Negative correlation between school bullying and multi-dimensional health in adolescent female migrants: a digital visual analog scale study - Song, Yueping; Li, Yifei; Zhou, Kai; Tang, Jia; Chen, Xuemeng; Liu, Gaowang (Frontiers in Psychology, 2025)
IntroductionSchool bullying poses significant risks to the physiological and psychological health of female adolescent migrants, a vulnerable group often overlooked during their critical developmental period. This study investigates the specific correlations between different types of bullying exposure and multi-dimensional health outcomes among female high school students aged 15 to 18 in China.MethodsData were derived from a longitudinal observational cohort, including clinical records and structured survey assessments. We introduced a novel digital visual analog scale (VAS) to quantify psychological tendencies (e.g., depressive symptoms, sleep disturbances) and physiological indicators (e.g., menstrual irregularities, EEG/ECG variations). Participants were categorized into five groups: violent bullying, multiple bullying, verbal bullying, social bullying, and a non-bullied control group. Statistical analyses were performed to compare health outcomes across these groups.ResultsStudents subjected to violent and multiple bullying exhibited markedly higher levels of physiological dysfunction and psychological distress compared to the control group. Verbal and social bullying also resulted in significant psychological symptoms. The severity of bullying showed a positive correlation with elevated VAS scores, indicating a dose-response relationship. These findings underscore the profound impact of school bullying on the health of female adolescent migrants.DiscussionThe results highlight an urgent need for targeted early detection and intervention strategies for this population. The digital VAS developed in this study proves to be an effective and sensitive tool for educators and clinicians to monitor and address the adverse health outcomes of bullying. These findings call for integrated support systems that address both the physical and mental health of vulnerable adolescents.